SAT0452 Influence of antirheumatic therapy administered in accordance with "treat to target" principles on heart rate variability and cardiovascular risk factors in patients with active early psoriatic arthritis. (15th June 2017) - Markelova, E; Novikova, D; Korotaeva, T; Loginova, E; Kirillova, I; Denisov, L; Karateev, D
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory arthropathy, which is associated with range of co-morbid diseases and risk factors, such as dyslipidemia, obesity, metabolic syndrome, cardiovascular disease (CVD). Lower heart rate variability (HRV) is a well-established risk factor for CVD and all-cause mortality in the general population. Objectives: to study dynamic of traditional risk factors (TRF) of CVD and parameters of HRV during antirheumatic therapy, administered inaccordance with "Treat to target" principles in PsA pts. Methods: 44 (F.-21) DMARD-naive PsA pts, according to the CASPAR criteria, age 36 [27; 46] years (yrs.), PsA duration – 6 [4; 8] yrs, DAS 4.06 [3.51; 4.74]. TRFs of CVD were assessed according to ESC (2016): arterial hypertension (AH) – 11 (22.9%) pts, obesity (body mass index >30kg/m 2 ) – 11 (22.9%), abdominal obesity – 14 (29.2%), dyslipidemia – 31 (64.5%), family history of early CVD – 6 (12.5%), menopausal status – 5 (10.4%), smoking - 16 (33.3%). All pts were assessed for ECG, 24-h ECG monitoring, carotid ultrasound imaging. Antihypertensive therapy received all pts with AH. Methotrexate (MT) therapy was started in all pts with an escalation of the dose up to 25 mg/week subcutaneously. In case of no remission 3 months later, MT was added with biologic therapy: Adalimumab, Certolizumabpegol, Ustekinumab. 23 subjects were assessed after 18 months of therapy. Results: After 18 months of therapy DAS and CRP level decreased significantly, p=0.001. DAS remission was achieved in 82.6% of pts. The incidence rate of AH (39% vs 39%), obesity (30% vs 21%), smokers (39% vs 39%), menopausal status (17% vs 17%), atherosclerotic plaques (39% vs 39%), did not change significantly. High-density lipoproteins increased significantly from 1.2 [1.1; 1.6] to 1.5 [1.2; 2.1]mmol/l, p=0.03. We didn't find significant differences between baseline and after treatment levels of total cholesterol/low-density lipoproteins level: from 5.2 [4.6; 6.0] to 5.2 [4.5; 5.9] (p=0.47) mmol/l and from 3.4 [2.8; 3.8] to 3.3 [2.6; 3.6] (p=0.60) mmol/l. HRVs parameters didn't change significant (table 1 ). Conclusions: antirheumatic therapy of early PsA pts in accordance with "T2T" principles improves lipid profile but not HRVs parameters. Lower HRV is a risk factor for cardiovascular disease and mortality that demands the further studying its influence on the cardiovascular prognosis in PsA pts. Disclosure of Interest: None declared